2006
DOI: 10.1124/mol.106.030817
|View full text |Cite
|
Sign up to set email alerts
|

Probing HIV-1 Integrase Inhibitor Binding Sites with Position-Specific Integrase-DNA Cross-Linking Assays

Abstract: HIV-1 integrase binds site-specifically to the ends of the viral cDNA. We used two HIV-1 integrase-DNA cross-linking assays to probe the binding sites of integrase inhibitors from different chemical families and with different strand transfer selectivities. The disulfide assay probes cross-linking between the integrase residue 148 and the 5Ј-terminal cytosine of the viral cDNA, and the Schiff base assay probes cross-linking between an integrase lysine residue and an abasic site placed at selected positions in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
28
0

Year Published

2007
2007
2011
2011

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 38 publications
(31 citation statements)
references
References 38 publications
3
28
0
Order By: Relevance
“…Although some attributed the position of 5CITEP to physical entrapment during crystallization (crystal packing), recent biochemical data confirmed some of the contacts observed by Goldgur et al . [10], but showed that 5CITEP, though presenting some structural features of INSTIs, resembles more a 3'P inhibitor [10], in line with enzyme inhibition data in the presence of Mg ++ ( i.e . the metal thought to act as a cofactor in vivo ) [18].…”
Section: Introductionmentioning
confidence: 60%
See 1 more Smart Citation
“…Although some attributed the position of 5CITEP to physical entrapment during crystallization (crystal packing), recent biochemical data confirmed some of the contacts observed by Goldgur et al . [10], but showed that 5CITEP, though presenting some structural features of INSTIs, resembles more a 3'P inhibitor [10], in line with enzyme inhibition data in the presence of Mg ++ ( i.e . the metal thought to act as a cofactor in vivo ) [18].…”
Section: Introductionmentioning
confidence: 60%
“…A credible theory sees 3'P inhibitors as docking at the HIV-1 DNA-binding site, and INSTIs as occupying the position of acceptor DNA [1,10]. This theory is supported by biochemical evidence [10,11]. IN inhibitors currently in clinical trials belong to the INSTI group.…”
Section: Introductionmentioning
confidence: 99%
“…5A, right panel). RAL did not significantly inhibit the 3Ј-P reaction in vitro, as expected for an INSTI compound (14,21,29). This assay, which used short blunt ODNs, also revealed that the ST reaction was impaired for both mutants.…”
Section: In Vitro Activity Of Y143r/c In Mutantsmentioning
confidence: 84%
“…[13,18] Through mutagenesis and photo-crosslinking studies, several amino acids that are involved in the DNA binding of IN, in particular Tyr143, have been identified, although these do not belong directly to the catalytic site of the enzyme. [19,20] In this work, pursuing our goal to identify novel HIV-1 IN inhibitors capable of blocking the IN-viral DNA interaction, and taking into account structure-activity relationship studies performed on the previous set of compounds, [17] we synthesized three new series of second-generation salicylic acid derivatives (A, B, and C in Figure 2). These compounds were designed to investigate the influence of synthetic derivatizations at position 5 of the furan ring, keeping the 2-salicylic furan moiety fixed.…”
Section: Introductionmentioning
confidence: 99%